Juan Ramón Jiménez: Of Naked Poetry and The Master Poet (1916-1936) - Graciela Palau de Nemes (Studies in 20th & 21st Century Literature, 1983)
The phrase naked poetry was coined by Juan Ramón Jiménez in 1916 and represents a style which influenced an outstanding generation of poets in twentieth-century Spain, among them Jorge Guillén, Pedro Salinas, Rafael Alberti, Luis Cernuda, Vicente Aleixandre and many others. This symbol is rooted in a sublimated concept of the essential naked woman, his wife, loved and possessed by the poet. At the same time it represents an essential poetry, devoid of all external adornment. It was used by Jiménez immediately after his marriage in a short poem which traces a parallel between the evolution of his poetic style and the sentimental episodes of his love life. It is related to disrobing (desnudar), a verb which originated in Spain with a mystical connotation meaning "to give up," "to deprive oneself," "to renounce." In the poetic career of Jiménez it is the point of departure for an artistic asceticism which leads to the neomystic union with a divinity described in Animal de fondo (Animal of the Depth), his last major work, of 1949. In the years of the preeminence of Jiménez (1916-1936), Spanish and foreign critics had great trouble explaining his new style. They called it stark, stripped, cryptic; they said that it created, aesthetically, a sense of incompleteness; that it turned sensations into concepts; that it expressed all which in nature is incapable of concrete realization. A review of this early criticism helps to convey the character of Jiménez' naked poetry in the years when he became the master poet of Spain.
Keywords: Juan Ramón Jiménez; naked poetry; Jorge Guillén; Pedro Salinas; Rafael Alberti; Luis Cernuda; Vicente Aleixandre; mysticism; desnudar; disrobing; poetic career; artistic asceticism; neomystic union; divinity; Animal de fondo; Animal of the Depth; poetic criticism; literary criticism